2020
DOI: 10.1177/1078155220968150
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab treatment for metastatic thymic epithelial tumors

Abstract: Background Metastatic and unresectable thymoma (T) or thymic carcinoma (TC) have limited treatment options, especially after first line. Methods Patients with unresectable or recurrent thymic tumors who used minimum one dose of nivolumab at any line of treatment were evaluated retrospectively. Even though nivolumab was administered 3mg/kg dosage in PRIMER study, due to toxicity and financial concerns, we used low dose regimen mostly. Results Among 46 unresectable and recurrent thymic epithelial tumors; 8 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Ak et al explored their experience with nivolumab for metastatic thymic epithelial tumors [ 13 ]. Among the 46 unresectable and recurrent thymic epithelial tumors (32 thymoma and 14 TC), 8 (3 TC, 4 thymoma, and one mixed histology of thymoma and TC) received nivolumab.…”
Section: Resultsmentioning
confidence: 99%
“…Ak et al explored their experience with nivolumab for metastatic thymic epithelial tumors [ 13 ]. Among the 46 unresectable and recurrent thymic epithelial tumors (32 thymoma and 14 TC), 8 (3 TC, 4 thymoma, and one mixed histology of thymoma and TC) received nivolumab.…”
Section: Resultsmentioning
confidence: 99%
“…12 The occurrence of severe irAEs has been linked with nivolumab treatment, even after a single dose, with some conditions persisting even after the cessation of therapy. 13 Further studies 14,15 reported higher grade irAEs, including myocarditis and myasthenia gravis, in thymoma patients than in patients with other cancer types. One report 10 recommended a regimen involving a half-dose of immunotherapy drug to achieve remission of the tumor, whilst incurring only mild irAEs.…”
Section: Discussionmentioning
confidence: 98%
“…The disease control rate (DCR) was 73%, the mPFS was 3.8 months and the mOS was 14.1 months, while the toxicity profile was manageable ( 29 ). Ak and Aydiner retrospectively tested the efficacy of nivolumab at four TMs, three TCs, and one mixed histology ( 30 ). Two patients' evaluation of best response was not applicable.…”
Section: Immunotherapy In Tetsmentioning
confidence: 99%
“…The median follow-up time was 16.1 months. The mPFS and mOS were 6.5 months and 7.4 months, respectively ( 30 ).…”
Section: Immunotherapy In Tetsmentioning
confidence: 99%